Earthquake Activities along the Ranong-Klong Marui Fault Zone, Southern Thailand: Implication from the Seismicity Data - Pailoplee, Santi (Bulletin of Earth Sciences of Thailand, 2021)
In this study, the earthquake activities along the Ranong-Klong Marui Fault Zone (RKFZ) are investigated using the power law of earthquake frequency-magnitude distribution (FMD). The possible maximum magnitudes, recurrence periods, including the probabilities of earthquake occurrences are determined according to the constant a- and b-values obtained from the FMD. The results reveal that the RKFZ has a potential to generate the earthquake with 6.3 and 6.9 Mw in the next 50 and 100 years. Meanwhile, the Mw-7.4 earthquake proposed previously as the maximum credible earthquake has the return period around 230 year. Moreover, for the probabilities of the Mw-7.4 occurrences in the next 10, 25, 50, and 100 years, this study concludes that there are around 4, 10, 20, and 36%, respectively.